Statistical comparison of the spatial distribution of both coffee leaf miner and predatory wasps - Costa, Franciella Marques da; Alves, Gabriella de Freitas; Scalon, João Domingos; Zacarias, Mauricio Sergio (Coffee Science - ISSN 1984-3909, 2015)
The coffee plant is subject to pests that can cause considerable damage to the producer. The pest that concerns most the Brazilian coffee growers is the coffee leaf miner (Lepidoptera: Lyonetiidae). One way to make the biological control of the coffee leaf miner is through predatory wasps (Hymenoptera: Vespidae). Researchers claim that for performing this type of control is important to know the spatial distribution in the coffee plantation of both the coffee leaf miner and the predatory wasp. There is also evidence that the spatial distribution of these species can be influenced by weather conditions. The aim of this work was to test whether or not there is a difference between the spatial distributions of mined leaves, predated mines and predatory wasps in different weather conditions. Data were obtained in 2006 from one hectare of organic coffee production, located in the county of Santo Antônio do Amparo, Brazil. To test the hypothesis of equality between two spatial distributions it was applied the Syrjala’s test. The results were: there was no difference between the spatial distribution of both mined leaves and predated mines during the dry and rainy seasons; mined leaves and predatory wasps showed the same spatial distribution for both in the dry and in the month of peak of the pest infestation; spatial distributions of predated mines and predatory wasps were different for both in the dry and in the month of greatest pest infestation. It is observed that there was no change in the spatial distribution of the leaf miner from the rain to the dry season. Equality in the spatial distribution of mined leaves and predatory wasps, suggests that wasps naturally seek the leaf miner.